Pentagone: patrolling BMP morphogen signaling. - Vuilleumier, R.; Affolter, M.; Pyrowolakis, G. (Fly, 2011)
Orchestration of spatial organization by signaling gradients--morphogen gradients--is a fundamental principle in animal development. Despite their importance in tissue patterning and growth, the exact mechanisms underlying the establishment and maintenance of morphogen gradients are poorly understood. Our recent work on BMP (bone morphogenetic protein) morphogen signaling during wing development identified a novel protein, Pentagone (Pent), as a critical regulator of morphogen activity. In the following, we discuss the properties of Pent and its role as a feed-back loop in morphogen gradient formation.